The Digital Workforce Challenge: Mapping Soft Skills For Future-Ready Graduates - Sari Marliani; July Yuliawati; Hendro Iwan Pradipto; Muhammad Akhdiyatul'aein; Febriyan Muliany; Aryanti Agustian; Isniar Budiarti (Dinasti Publisher, 2025)
This study's objectives are to assess the level of soft skill mastery among students, identify any issues that arise, and develop effective growth strategies. Soft skills are a crucial component in today's increasingly digital and dynamic workplace. This study assesses the mastery of soft skills as well as the strategy and tactics for developing them. A mixed-method approach was used to gather information: questionnaires were sent to 200 students, 50 students were given soft skill tests based on case studies, 10 students, 5 students, and 5 employees were interviewed, and the curriculum and report were analyzed. The study's findings indicate that the student has excellent communication skills (3.7) and teamwork (3.9), but is somewhat lacking in flexibility (2.9) and leadership (3.1). These soft skills emphasize that, while a student can solve problems in a straightforward manner, they struggle to deal with complex situations that require innovation and multidisciplinary teamwork. Interview and document analysis indicate that curriculum adherence and practical experience are crucial for developing soft skills. This study highlights the need for curriculum revision based on student feedback, increased access to learning, and the use of digital technology in education. It comes from combined research that looks at competency, what that means for the Chinese education system, and how to build soft skills through long-term experience. It is believed that this will serve as a foundation for educational institutions to implement more effective policies to increase student engagement